Pengaruh Komunikasi Pemasaran terhadap Keputusan Pembelian Konsumen Lipstik Brand Implora di Toko Jenny Shop Bondowoso - Agustin, Isna; Latif Najmuddin, Abdul; Fauzi, Ahmad (Medio Jurnal Ilmu Komunikasi, 2024)
Jhenny Shop is a shop that operates in the cosmetics sector. Purchasing decisions are still very important for the shop, purchasing decisions often occur that do not meet standards, this is caused by marketing strategies that are not well thought out and sales processes that are not properly monitored. Consumer purchasing decisions are the process by which each person considers various options and chooses one for a particular product. The large number of new products requires retailers to act as companies that offer various goods to consumers so that they can analyze the factors that form the basis of the consumer decision-making process in carrying out measurements of products that have been set aside. The aim of this research is to determine the influence of marketing communications on consumer purchasing decisions. The sampling method used a questionnaire of 57 respondents. Then analyzed using quantitative methods. The data analysis methods used are, linear regression test, classic assumption test which includes normality test, multicollinearity test, and heteroscedasticity test, then hypothesis test and coefficient of determination. With the independent variable Marketing Communication, the results of this analysis show that there is an influence of Marketing Communication on consumer purchasing decisions.